A substituição de importações no Brasil entre 1995 e 2000 - Franco, Ana Maria de Paiva (2005)
This work estimates the import substitution process in Brazilian industrial sectors in a recent period and evaluates whether it is occurring naturally or is in part induced by some kind of external commercial policy. An index to measure import substitution was calculated for forty nine sectors of industry. A regression analysis with this index against effective tariffs and real effective exchange rate, during the period 1995-2000, shows that these variables (effective tariffs and real effective exchange rates) did affect the substitution index. From 1999 on, the influence of the exchange rate over the import substitution index was greater than the influence of the effective tariff, suggesting that the process of import substitution post the Brazilian currency depreciation occurred in 1999 contains elements that characterizes it as a "natural" process.